Optimizing the performance of auxetic square tubes under uniaxial compression - Atilla Yolcu, Dilek; İlgen, Fatih; Okutan Baba, Buket (Mechanics of advanced materials and structures, 2024)
Thin-walled tubes are widely used as energy absorbers to increase the crash resistance and safety while maintaining lightness. There has been an increase in interest in the integration of auxetic structures into these tubes. This is due to the better mechanical strength displayed by auxetic structures with negative Poisson's ratio, particularly in terms of compressive behavior and energy absorption. In this study, a group of square-section tubes with different types of cell structures on their side faces was examined. Under quasi-static compression, the behaviors of thin-walled square tubes with reentrant auxetic and conventional honeycomb were examined numerically and experimentally. In addition, geometric optimization of reentrant cell shape was performed to maximize the compressive loading of the square tubes. First, the compression behaviors of thin-walled square tubes made of polylactic acid (PLA) were examined; these tubes' side surfaces have both conventional and reentrant auxetic honeycomb cellular patterns. The reentrant auxetic and conventional honeycomb cell architectures were applied together and separately on the side faces of the thin-walled tube, with the identical cell parameters. In order to better understand the deformations, force-displacement curves were examined for four different types of thin-walled square tubes, including tubes with reentrant auxetic and honeycomb cell structures on all side faces and tubes with these structures on opposite sides and adjacent. Using the ANSYS finite element software package and Digimizer image processing programs, the Poisson's ratio of the reentrant auxetic and conventional honeycomb configurations as well as the maximum compression force of the tubular structures were determined numerically and experimentally. After obtaining the result that the use of the reentrant auxetic structure on the side surfaces of the square tube significantly increased the compression resistance and energy absorption capability of the tube, the optimization of the square tube with the reentrant auxetic structure on all surfaces was examined. The effect of the geometrical parameters such as ligament length, reentrant angle, and cell thickness of the unit-cell on the compression load of the square tube was investigated using an integrated methodology combining numerical simulation and DoE (Design of Experiments) method. The findings show that the tubes combined reentrant auxetic structure exhibits better energy absorption than the conventional honeycomb tubes. It also reveals that the optimum geometric parameters of the reentrant auxetic unit cell are to be the ligament length of 16.358 mm, the ligament angle of 80°, and the ligament thickness of 3 mm.